2011
DOI: 10.1007/s12038-011-9020-6
|View full text |Cite
|
Sign up to set email alerts
|

P1 peptidase – a mysterious protein of family Potyviridae

Abstract: The Potyviridae family, named after its type member, Potato virus Y (PVY), is the largest of the 65 plant virus groups and families currently recognized. The coding region for P1 peptidase is located at the very beginning of the viral genome of the family Potyviridae. Until recently P1 was thought of as serine peptidase with RNA-binding activity and with possible influence in cell-to-cell viral spreading. This N-terminal protein, among all of the potyviruses, is the most divergent protein: varying in length an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 110 publications
1
25
0
Order By: Relevance
“…P1 is the least conserved protein in PVV-phureja sharing 70-77% amino acid identity with homologs within the PVV group in agreement with previous observations, which showed P1 to be the protein most variable in size and sequence within the genus Potyvirus (Rohozková and Navrátil, 2011). A recent study in tobacco etch virus (TEV) has shown P1 to contain nucleolar localization and nuclear export signals that allow its traffi c in and out of the nucleus and nucleolus during infection (Martínez and Daròs, 2014).…”
Section: Genome Sequence Propertiessupporting
confidence: 87%
“…P1 is the least conserved protein in PVV-phureja sharing 70-77% amino acid identity with homologs within the PVV group in agreement with previous observations, which showed P1 to be the protein most variable in size and sequence within the genus Potyvirus (Rohozková and Navrátil, 2011). A recent study in tobacco etch virus (TEV) has shown P1 to contain nucleolar localization and nuclear export signals that allow its traffi c in and out of the nucleus and nucleolus during infection (Martínez and Daròs, 2014).…”
Section: Genome Sequence Propertiessupporting
confidence: 87%
“…Besides the self-cleavage activity intrinsic to its C-terminal end, other activities of potyviral P1 and its real contributions to viral replication remained vague, so much so that P1 earned the appellative “mysterious protein” in a recent review [24].…”
Section: Discussionmentioning
confidence: 99%
“…NIb is the viral RNA-dependent RNA polymerase (14), and CP, in addition to virion assembly, is involved in aphid transmission (15) and viral movement (16). In contrast, P1, the first product of potyviral polyprotein, is a rather mysterious protein whose functions during the infectious cycle are mostly unknown (17). The P1 cistron is the most variable in size and sequence in the various species of the genus (18).…”
Section: In This Work We Researched the Role During Infection Of Tobmentioning
confidence: 99%